Surface treatment method of aluminum alloy material and nano self-repairing aluminum alloy material
Through electrolyte plasma polishing and polyacrylic nano-self-repair technology, the damage and uneven roughness problems of traditional mechanical polishing on the surface of aluminum alloy are solved, and efficient polishing and long-term self-repair of aluminum alloy surfaces are achieved, which improves reflectivity and durability , reduces costs.
Patent Information
- Application Number
- CN202411383781.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional mechanical polishing methods have severe damage to the surface of aluminum alloy, resulting in uneven surface roughness, affecting reflectivity and heat collection efficiency, and are cost-effective and inefficient.
Electrolyte plasma polishing combined with polyacrylic acid nano-self-healing technology is used to remove microscopic protrusions and depressions on the surface of the aluminum alloy through electrolyte plasma polishing, and coat polyacrylic acid nano-self-healing materials to form a wear-resistant and corrosion-resistant protective layer.
It realizes efficient polishing and long-term self-repair of aluminum alloy surfaces, reduces surface roughness, improves reflectivity and durability, and reduces production and maintenance costs.
Smart Images

Figure CN119243308A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy surface treatment, and in particular to a surface treatment method of an aluminum alloy material and a nanometer self-repairing aluminum alloy material. Background Art
[0002] Developing large-scale clean energy to meet large-scale power generation needs is an important means to solve the environmental energy crisis. Solar thermal power generation is one of the power generation modes that can be commercialized. The reflectivity of the heliostat is proportional to its heat collection efficiency and is an important component for realizing solar thermal power generation.
[0003] Traditional glass silver-plated heliostats are heavy, costly, and pose safety hazards during transportation and installation, and their reflectivity is also limited. In order to reduce the cost of solar thermal power generation heliostats, aluminum mirrors can be silver-plated instead of traditional glass silver-plated heliostats. Aluminum mirrors have the advantages of light weight, low cost, and excellent reflective performance. However, due to the presence of oxide film and roughness on the surface of aluminum alloys, surface polishing of aluminum alloys has always been a difficult problem. The traditional mechanical polishing method is to achieve surface polishing by removing the protruding parts through cutting and surface plastic deformation. This method is often inefficient, costly, and requires a long time and a high level of skill, and has a large wear on polishing tools and equipment; and it is easy to damage the surface of the material during the polishing process, such as scratches, resulting in uneven surface roughness of the material. The rough aluminum substrate is not conducive to subsequent silver plating, which will reduce the reflectivity of the heliostat, thereby reducing the heat collection efficiency. Therefore, it is of great significance to develop an efficient aluminum alloy polishing and self-repairing process. Summary of the invention
[0004] In order to solve the problem that traditional mechanical polishing methods easily damage the material surface during the polishing process, resulting in uneven surface roughness of the material, the purpose of the present invention is to provide a surface treatment method for aluminum alloy materials and nano self-repairing aluminum alloy materials.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] A first aspect of the present invention provides a surface treatment method for an aluminum alloy material, comprising the following steps:
[0007] The aluminum alloy material to be polished is immersed in an electrolytic polishing liquid, and then the electrolyte plasma polishing is performed at 60 to 90° C. The voltage of the electrolyte plasma polishing is 240V to 320V to obtain a polished aluminum alloy material;
[0008] The polyacrylic acid nano self-repairing material is coated on the surface of the polished aluminum alloy material, and the coating is cured to obtain the nano self-repairing aluminum alloy material; the mass percentage of polyacrylic acid in the polyacrylic acid nano self-repairing material is 10wt% to 50wt%.
[0009] The present invention combines PeP polishing with PAA nano self-repairing technology to precisely control the surface morphology of the aluminum alloy, and polishes and removes and repairs microscopic protrusions and depressions on the surface of the aluminum alloy respectively; the PeP process reduces the generation of mechanical stress and scratches during the polishing process, and improves the polishing quality and efficiency; the PAA nano self-repairing technology can not only repair the sub-surface defects of the aluminum alloy, but also improve the hardness of the aluminum alloy surface to a certain extent, making it more wear-resistant and scratch-resistant and preventing it from further corrosion and oxidation, thereby solving the problem that the traditional mechanical polishing method is easy to damage the material surface during the polishing process, resulting in uneven surface roughness of the material.
[0010] Preferably, the electrolytic polishing solution is obtained by dissolving an electrolyte in water;
[0011] The electrolyte is obtained by mixing potassium chloride, ammonium chloride and organic acid;
[0012] The concentration of potassium chloride in the electrolytic polishing liquid is 10wt%; the concentration of ammonium chloride in the electrolytic polishing liquid is 40wt%; the concentration of organic acid in the electrolytic polishing liquid is 1-5wt%; the organic acid is citric acid or oxalic acid. The electrolyte of the electrolytic polishing liquid can be selected according to actual needs. For example, the electrolyte of the electrolytic polishing liquid can also use ferric chloride, triethanolamine, EDTA, ferric sulfate, ammonium sulfate, etc. as the formula components of the electrolyte.
[0013] Preferably, the polyacrylic acid nano self-healing material is obtained by mixing polyacrylic acid with water.
[0014] Preferably, the molecular weight of the polyacrylic acid is 2000Da to 5000Da. The polyacrylic acid is nano-water-based low molecular weight polyacrylic acid.
[0015] Preferably, the temperature of the electrolyte plasma polishing is 90° C.±2° C. The polishing temperature is between 60° C. and 90° C., preferably 90° C.±2° C., to ensure that the temperature of the electrolytic polishing solution is uniform and stable.
[0016] Preferably, the voltage of the electrolyte plasma polishing is 240V to 280V.
[0017] Preferably, the electrolyte plasma polishing time is 1 min to 9 min.
[0018] Preferably, the aluminum alloy material to be polished is immersed in an electrolytic polishing solution, and then subjected to electrolyte plasma polishing at 60 to 90° C., specifically:
[0019] The aluminum alloy material to be polished is connected to the anode of the power supply, and the conductive material is connected to the cathode of the power supply, and the aluminum alloy material to be polished and the conductive material are immersed in an electrolytic polishing liquid at 60 to 90° C., and then electrolyte plasma polishing is performed at a voltage of 200V to 400V to obtain a polished aluminum alloy material; the conductive material is titanium, for example, a pure titanium sheet or a pure titanium rod.
[0020] Preferably, the coating is cured, specifically by drying the aluminum alloy material coated with the polyacrylic acid nano self-healing material, at a drying temperature of 100°C to 180°C for 10 minutes to 20 minutes, to ensure that the coating of the polyacrylic acid nano self-healing material is uniformly cured on the surface of the aluminum alloy material to form a dense protective film. Preferably, the drying method is segmented drying, specifically: first drying at 180°C for 10 minutes, and then drying at 100°C for 5 minutes.
[0021] The second aspect of the present invention provides a nano self-repairing aluminum alloy material prepared by the surface treatment method described in the first aspect.
[0022] Preferably, the surface arithmetic mean roughness of the nano self-repairing aluminum alloy material is 0.1-0.2 μm; and the average height difference between surface peaks and valleys is 2-4 μm.
[0023] Beneficial effects of the present invention:
[0024] 1. The present invention combines electrolyte plasma polishing with polyacrylic acid nano self-repairing technology to achieve efficient polishing and long-term self-repairing protection of the aluminum alloy surface, thereby obtaining an extremely smooth and durable aluminum alloy surface morphology, solving the problem that traditional mechanical polishing methods easily damage the material surface during the polishing process, resulting in uneven surface roughness of the material.
[0025] 2. The arithmetic mean roughness of the aluminum alloy surface treated by the method of the present invention can be as small as 0.1 μm, and the average height difference between the surface peaks and valleys can be as small as 2 μm.
[0026] 3. The method of the present invention improves the processing quality and protective performance of the aluminum alloy surface, reduces the production cost and maintenance cost, has good application prospects and market value, and promotes the innovative development of aluminum alloy surface treatment technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The scanning electron microscope images of the aluminum alloy workpiece to be polished, wherein (b) is a partial enlarged image of (a).
[0028] Figure 2 The scanning electron microscope image of the nano self-repairing aluminum alloy material obtained after the treatment in Example 1. Among them, Figure (b) is a partial enlarged image of Figure (a).
[0029] Figure 3 It is the reflectivity trend line in the wavelength range of 400nm to 700nm after silver plating on different substrates.
[0030] Figure 4 The curves of Sa changing with voltage under different oxalic acid concentrations.
[0031] Figure 5 The curves of Sz changing with voltage at different oxalic acid concentrations.
[0032] Figure 6 This is the curve showing the change of reflectivity with polishing voltage in the wavelength range of 400nm to 700nm under different oxalic acid concentrations.
[0033] Figure 7 This is a graph showing the change in total reflection in the wavelength range of 400nm to 700nm as a function of polishing voltage under different oxalic acid concentrations.
[0034] Figure 8 This is the curve of Sa changing with time under different PeP voltages.
[0035] Fig. 9 This is the curve of Sz changing with time under different PeP voltages.
[0036] Fig.10 This is the curve showing the change of reflectivity with polishing time in the wavelength range of 400nm to 700nm under different PeP voltages.
[0037] Fig.11 This is a graph showing the change in total reflection in the wavelength range of 400nm to 700nm with polishing time under different PeP voltages. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0040] Currently, the commonly used polishing processes for aluminum alloys include: mechanical polishing, chemical polishing, electrochemical polishing, ultrasonic polishing, fluid polishing, magnetic grinding polishing, etc.
[0041] Mechanical polishing is the process of removing protrusions through cutting and surface plastic deformation, but scratches and uneven surface roughness may occur during the polishing process, and it requires a long time and a high level of skill, and causes greater wear and tear on polishing tools and equipment.
[0042] Chemical polishing is to place aluminum alloy die-castings in a chemical medium. Since the microscopic protrusions have a larger surface area and are more easily corroded by the chemical liquid, they are dissolved first, thereby obtaining a smooth surface. However, defects such as gas streaks and dark spots may be generated during the polishing process. The chemical components in the chemical polishing liquid may cause pollution to the environment, and the polishing liquid needs to be replaced regularly, which increases costs.
[0043] Electrochemical polishing mainly utilizes the principle of electrochemical anode dissolution. High-concentration acid is used as the electrolytic polishing liquid. During the electrolysis process, the aluminum alloy on the anode surface is dissolved and corroded, thereby achieving grinding and polishing. The main drawback is that the polishing liquid uses an acid or alkaline solution, which will cause pollution to the environment.
[0044] Ultrasonic polishing is to immerse aluminum alloy die-castings in an abrasive suspension and place them in an ultrasonic field, using the oscillation of ultrasound to perform grinding and polishing. The disadvantage is that the manufacture and installation of ultrasonic polishing equipment is relatively difficult, and the abrasive suspension needs to be replaced regularly, which increases the complexity of the operation. In addition, the ultrasonic polishing effect is greatly affected by the ultrasonic frequency and power, and it is difficult to determine the optimal polishing parameters.
[0045] Fluid polishing uses high-speed flowing liquid and carried abrasive particles to flush the surface of aluminum alloy die-castings to achieve the polishing effect. Common methods include abrasive jet processing, liquid jet processing and fluid dynamic grinding. The disadvantage is that a large amount of water and abrasives are consumed during the fluid polishing process, which increases the cost. At the same time, the polishing effect is greatly affected by the fluid flow rate and abrasive particle size, and it is difficult to accurately control the parameters to obtain uniform surface quality.
[0046] In order to solve the problems existing in traditional polishing methods, electrolyte plasma polishing came into being. Electrolyte plasma polishing, referred to as PeP, uses specific ions in the electrolyte solution to form a group of active particles in a plasma state under the action of an electric field. These high-energy active particles react physically and chemically with the surface of the material to remove tiny protrusions, burrs and uneven layers on the surface. However, electrolyte plasma polishing mainly solves surface protrusions and burrs, but cannot completely remove scratches, holes and depressions on the surface of aluminum alloys.
[0047] Based on the above analysis, the present invention combines the PAA nano self-repairing technology on the basis of the electrolyte plasma polishing technology to perform self-leveling treatment on the surface of the aluminum alloy, further improve the surface quality of the aluminum alloy, and achieve an ultra-smooth mirror effect of the aluminum alloy.
[0048] The method of the present invention can achieve fine polishing of the aluminum alloy substrate and reduce the surface roughness of the aluminum alloy. The PAA nano self-repairing coating forms a nano layer with self-repairing function on the surface of the aluminum alloy. The nanoparticles in the PAA nano self-repairing coating can automatically fill the sub-surface defects of the aluminum alloy, restore the integrity of the surface, and improve the corrosion resistance of the aluminum alloy, extend the service life of the aluminum alloy, and provide good substrate conditions for subsequent silver plating and achieving ultra-high reflectivity.
[0049] The technical solution of the present invention is further described below through specific examples. In the following examples, the methods are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified. In the following examples, PeP is electrolyte plasma polishing. PAA is polyacrylic acid, and its molecular formula is (CH2-CHCO2H) n , molecular weight is 2000Da~5000Da. CA is citric acid. Sa is the arithmetic mean roughness of the surface; Sz is the average height difference between the peaks and valleys of the surface.
[0050] In the following embodiments, the aluminum alloy workpiece is any one of a 6061 aluminum alloy workpiece, a 6063 aluminum alloy workpiece, a 6082 aluminum alloy workpiece, a 7075 aluminum alloy workpiece, and a 5083 aluminum alloy workpiece; for the convenience of testing, the following embodiments are described using a 6061 aluminum alloy workpiece as an example.
[0051] Example 1
[0052] A surface treatment method for an aluminum alloy material comprises the following steps:
[0053] Step 1: add 10g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 1wt%.
[0054] Step 2, pour the electrolytic polishing liquid into the electrolytic tank until the appropriate liquid level, ensure that there are no impurities in the polishing tank and the liquid level is high enough to immerse the aluminum alloy workpiece to be polished; turn on the heating power supply, heat the electrolytic polishing liquid to 90 ° C, ensure that the electrolytic polishing liquid does not overflow during the heating process, and the heating equipment operates stably. The perforated aluminum alloy workpiece is ultrasonically cleaned and hung on the hanger. The fixture holding the aluminum alloy workpiece is connected to the anode of the power supply, and the pure titanium rod is connected to the cathode of the power supply as the cathode material. The aluminum alloy workpiece and the cathode material are completely immersed in the electrolytic polishing liquid heated to 90 ° C, the high-voltage DC power supply is turned on, and a high voltage of 320V is applied for PeP polishing, and the polishing time is 5min. After polishing is completed, the aluminum alloy material after PeP polishing is taken out of the electrolytic polishing liquid and immediately placed in anhydrous ethanol for ultrasonic cleaning to remove the residual polishing liquid and impurities on the surface of the workpiece; then dehydrated and placed in an oven for drying to ensure that the surface of the aluminum alloy workpiece is dry and free of moisture to obtain a polished aluminum alloy workpiece.
[0055] Step 3, add polyacrylic acid with a molecular weight of 2000Da to pure water, and control the concentration of polyacrylic acid to be 10wt%. Fix the polished aluminum alloy workpiece on a plane, and evenly coat the prepared PAA nano self-healing material on the surface of the aluminum alloy workpiece to ensure that the coating is uniform and of moderate thickness. Put the aluminum alloy workpiece coated with PAA into an oven for drying at a temperature of 180°C for 15 minutes to solidify the coating, thereby obtaining a nano self-healing aluminum alloy material with nano self-healing function, referred to as nano self-healing aluminum alloy material, with a smooth surface morphology, Sa = 0.165μm; Sz = 3.897μm.
[0056] Scanning electron microscope analysis: The aluminum alloy workpiece to be polished was subjected to scanning electron microscope analysis. The results are shown in Figure 1 The nano self-repairing aluminum alloy material obtained after the treatment in Example 1 was analyzed by scanning electron microscope. Figure 2 .
[0057] Depend on Figure 1 and Figure 2 It can be seen that before polishing, the surface of the aluminum alloy workpiece sample has large protruding particles. Figure 1 (a) and the surface of the aluminum alloy workpiece sample has obvious mechanical processing marks, see Figure 1 (b) of the figure. After the nano self-repairing aluminum alloy material was treated by the method of Example 1, the large particles protruding on the surface of the sample were removed, the mechanical processing marks were obviously removed, and the surface roughness was greatly reduced. It can be seen that the method of Example 1 of the present invention can significantly improve the brightness and reflective properties of the surface of the aluminum alloy workpiece sample.
[0058] Reflectivity test: The aluminum alloy workpiece to be polished is subjected to surface silver plating, and the obtained silver-plated sample is recorded as the pre-polishing sample. The polished aluminum alloy workpiece obtained in step 2 of Example 1 is subjected to surface silver plating, and the obtained silver-plated sample is recorded as the PeP polishing sample. The nano self-repairing aluminum alloy material obtained in step 3 of Example 1 is subjected to surface silver plating, and the obtained silver-plated sample is recorded as the PeP polishing + nano self-repairing sample. The pre-polishing sample, PeP polishing sample and PeP polishing + nano self-repairing sample are tested for reflectivity, and the reflectivity in the wavelength range of 400nm to 700nm is recorded. The results are shown in FIG. Figure 3 .
[0059] Depend on Figure 3 The results show that silver plating on different substrates has a great influence on the reflectivity of the obtained silver-plated samples. After PeP polishing, the surface is coated with a nano self-repairing coating and then silver-plated. The reflectivity of the silver-plated sample obtained is the highest, and the untreated aluminum alloy workpiece has the lowest reflectivity after silver plating. This further illustrates that the embodiment of the present invention combines PeP polishing with polyacrylic acid nano self-repairing technology to achieve efficient polishing and long-term self-repairing protection of the aluminum alloy surface, thereby obtaining an extremely smooth and durable aluminum alloy surface morphology and achieving ultra-high reflectivity.
[0060] From the above analysis, it can be seen that the nano self-repairing coating used in the embodiment of the present invention is a water-based low molecular weight polymer, which can repair nano-scale holes and defects on the surface of the aluminum alloy substrate, further repair the PeP polishing, improve the surface quality, improve the quality of the silver plating layer, and improve the reflective performance.
[0061] Example 2
[0062] A surface treatment method for an aluminum alloy material comprises the following steps:
[0063] Step 1, add 20g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 2wt%.
[0064] Step 2, pour the electrolytic polishing liquid into the electrolytic cell until the appropriate liquid level, turn on the heating power supply, and heat the electrolytic polishing liquid to 90°C. Ultrasonic clean the perforated aluminum alloy workpiece and hang it on the hanger. Connect the fixture holding the aluminum alloy workpiece to the anode of the power supply, and connect the pure titanium rod to the cathode of the power supply as the cathode material. Immerse the aluminum alloy workpiece and the cathode material in the electrolytic polishing liquid heated to 90°C, and apply a high voltage of 300V for PeP polishing. The polishing time is 5 minutes. After polishing, the aluminum alloy material after PeP polishing is ultrasonically cleaned, dehydrated and dried in anhydrous ethanol.
[0065] Step 3, add polyacrylic acid with a molecular weight of 2000Da into pure water, control the concentration of polyacrylic acid to 20wt%, and coat it on the surface of the aluminum alloy after drying. Put the aluminum alloy sample coated with polyacrylic acid into an oven, dry it at 180℃ for 15min, and solidify the coating to obtain a nano self-repairing aluminum alloy material with a smooth surface morphology, Sa=0.146μm; Sz=3.585μm.
[0066] Example 3
[0067] A surface treatment method for an aluminum alloy material comprises the following steps:
[0068] Step 1: add 30g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 3wt%.
[0069] Step 2, pour the electrolytic polishing liquid into the electrolytic cell until the appropriate liquid level, turn on the heating power supply, and heat the electrolytic polishing liquid to 90°C. Ultrasonic clean the perforated aluminum alloy workpiece and hang it on the hanger. Connect the fixture holding the aluminum alloy workpiece to the anode of the power supply, and connect the pure titanium rod to the cathode of the power supply as the cathode material. Immerse the aluminum alloy workpiece and the cathode material in the electrolytic polishing liquid heated to 90°C, and apply a high voltage of 280V for PeP polishing. The polishing time is 5 minutes. After polishing, the aluminum alloy material after PeP polishing is ultrasonically cleaned, dehydrated and dried in anhydrous ethanol.
[0070] Step 3, add polyacrylic acid with a molecular weight of 2000Da into pure water, control the concentration of polyacrylic acid to 30wt%, and coat it on the surface of the aluminum alloy after drying. Put the aluminum alloy sample coated with polyacrylic acid into an oven, dry it at 180℃ for 15min, and solidify the coating to obtain a nano self-repairing aluminum alloy material with a smooth surface morphology, Sa=0.145μm; Sz=3.548μm.
[0071] Example 4
[0072] A surface treatment method for an aluminum alloy material comprises the following steps:
[0073] Step 1, add 40g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 4wt%.
[0074] Step 2, pour the electrolytic polishing liquid into the electrolytic cell until the appropriate liquid level, turn on the heating power supply, and heat the electrolytic polishing liquid to 90°C. Ultrasonic clean the perforated aluminum alloy workpiece and hang it on the hanger. Connect the fixture holding the aluminum alloy workpiece to the anode of the power supply, and connect the pure titanium rod to the cathode of the power supply as the cathode material. Immerse the aluminum alloy workpiece and the cathode material in the electrolytic polishing liquid heated to 90°C, and apply a high voltage of 260V for PeP polishing. The polishing time is 5 minutes. After polishing, the aluminum alloy material after PeP polishing is ultrasonically cleaned, dehydrated and dried in anhydrous ethanol.
[0075] Step 3, add polyacrylic acid with a molecular weight of 2000Da into pure water, control the concentration of polyacrylic acid to 40wt%, and coat it on the surface of the aluminum alloy after drying. Put the aluminum alloy sample coated with polyacrylic acid into an oven, and dry it at a temperature of 180°C for 15 minutes to solidify the coating to obtain a nano self-repairing aluminum alloy material with a smooth surface morphology, Sa = 0.132μm; Sz = 3.218μm.
[0076] Example 5
[0077] A surface treatment method for an aluminum alloy material comprises the following steps:
[0078] Step 1, add 50g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 5wt%.
[0079] Step 2, pour the electrolytic polishing liquid into the electrolytic cell until the appropriate liquid level, turn on the heating power supply, and heat the electrolytic polishing liquid to 90°C. Ultrasonic clean the perforated aluminum alloy workpiece and hang it on the hanger. Connect the fixture holding the aluminum alloy workpiece to the anode of the power supply, and connect the pure titanium rod to the cathode of the power supply as the cathode material. Immerse the aluminum alloy workpiece and the cathode material in the electrolytic polishing liquid heated to 90°C, and apply a high voltage of 240V for PeP polishing. The polishing time is 5 minutes. After polishing, the aluminum alloy material after PeP polishing is ultrasonically cleaned, dehydrated and dried in anhydrous ethanol.
[0080] Step 3, add polyacrylic acid with a molecular weight of 2000Da into pure water, control the concentration of polyacrylic acid to 50wt%, and coat it on the surface of the aluminum alloy after drying. Put the aluminum alloy sample coated with polyacrylic acid into an oven, dry it at 180℃ for 15min, and solidify the coating to obtain a nano self-repairing aluminum alloy material with a smooth surface morphology, Sa=0.128μm; Sz=2.870μm.
[0081] Example 6
[0082] A surface treatment method for an aluminum alloy material comprises the following steps:
[0083] Step 1: add 30g of citric acid, 100g of ammonium chloride and 40g of potassium chloride into water, stir evenly, and fully mix the electrolyte with water to obtain an electrolytic polishing solution. The concentration of citric acid in the electrolytic polishing solution is 3wt%.
[0084] Step 2, pour the electrolytic polishing liquid into the electrolytic cell until the appropriate liquid level, turn on the heating power supply, and heat the electrolytic polishing liquid to 90°C. Ultrasonic clean the perforated aluminum alloy workpiece and hang it on the hanger. Connect the fixture holding the aluminum alloy workpiece to the anode of the power supply, and connect the pure titanium rod to the cathode of the power supply as the cathode material. Immerse the aluminum alloy workpiece and the cathode material in the electrolytic polishing liquid heated to 90°C, and apply a high voltage of 240V for PeP polishing. The polishing time is 5 minutes. After polishing, the aluminum alloy material after PeP polishing is ultrasonically cleaned, dehydrated and dried in anhydrous ethanol.
[0085] Step 3, add polyacrylic acid with a molecular weight of 2000Da to pure water, control the concentration of polyacrylic acid to 50wt%, and coat it on the surface of the aluminum alloy after drying. Put the aluminum alloy sample coated with polyacrylic acid into an oven, the drying temperature is 180℃, and the drying time is 10min; then dry it at 100℃ for 5min to solidify the coating, and obtain a nano self-repairing aluminum alloy material with a smooth surface morphology, Sa=0.111μm; Sz=2.027μm.
[0086] The surface roughness of the nano self-repairing aluminum alloy materials prepared in Examples 1 to 6 was measured, wherein the surface arithmetic mean roughness and the average height difference between the surface peaks and valleys are two important parameters for examining the surface roughness. For the convenience of description, the surface arithmetic mean roughness is represented by Sa; the average height difference between the surface peaks and valleys is represented by Sz. Sa more comprehensively reflects the overall roughness of the surface. The smaller the Sa value, the smoother the surface; the larger the Sa value, the rougher the surface. Sz gives the maximum fluctuation of the surface more intuitively. The smaller the Sz value, the smaller the maximum fluctuation of the surface, that is, the flatter the surface; the larger the Sz value, the larger the maximum fluctuation of the surface, that is, the more uneven the surface. The surface roughness measurement results of the nano self-repairing aluminum alloy materials of Examples 1 to 6 are shown in Table 1.
[0087] Table 1 Surface roughness measurement results
[0088] Citric acid concentration PeP parameters PAA concentration Sa value Sz value Example 1 1wt% 320V 10wt% 0.165μm 3.897μm Example 2 2wt% 300V 20wt% 0.146μm 3.585μm Example 3 3wt% 280V 30wt% 0.145μm 3.548μm Example 4 4wt% 260V 40wt% 0.132μm 3.218μm Example 5 5wt% 240V 50wt% 0.128μm 2.870μm Example 6 3wt% 240V 50wt% 0.111μm 2.027μm
[0089] It can be seen from the results in Table 1 that the Sa values of the nano self-repairing aluminum alloy materials prepared in Examples 1 to 6 are in the range of 0.111 μm to 0.165 μm; and the Sz values are in the range of 2.027 μm to 3.897 μm. Among them, the Sa value and Sz value of Example 6 are relatively small, and an extremely smooth and durable aluminum alloy surface morphology can be obtained, achieving ultra-high reflectivity.
[0090] Example 7
[0091] A surface treatment method for an aluminum alloy material is basically the same as the method in Example 1, except that the citric acid concentration and the PeP voltage are different, see Table 2.
[0092] Table 2 Comparison of reaction conditions at different citric acid concentrations and different PeP voltages
[0093]
[0094]
[0095] The surface roughness of the nano self-healing aluminum alloy materials prepared under different citric acid concentrations and different PeP voltages is measured. Among them, the surface arithmetic mean roughness and the average height difference between the surface peaks and valleys are two important parameters for examining the surface roughness. For the convenience of description, the surface arithmetic mean roughness is represented by Sa; the average height difference between the surface peaks and valleys is represented by Sz.
[0096] Using citric acid, ammonium chloride and potassium chloride as the formula of electrolytic polishing liquid, PeP polishing test was carried out on aluminum alloy workpiece, and the variables were citric acid concentration and PeP voltage. The selected citric acid concentrations were 1w%, 2w%, 3w%, 4w%, and 5w%. The selected PeP voltages were 240V, 250V, 260V, 270V, and 280V. The surface morphology and roughness were tested and analyzed using a laser confocal microscope. The surface roughness measurement results of nano self-healing aluminum alloy materials prepared under different citric acid concentrations and different PeP voltages are shown in Tables 3 and 4, as well as Figure 4 and Figure 5 .
[0097] Table 3 Sa values (μm) at different citric acid concentrations and different PeP voltages
[0098]
[0099] Table 4 Sz values (μm) at different citric acid concentrations and different PeP voltages
[0100]
[0101] Figure 4 and Figure 5The variation trend of the arithmetic mean roughness of the aluminum alloy workpiece and the average height difference of the surface peaks and valleys with the PeP voltage under different oxalic acid concentrations is shown. Figure 4 and Figure 5 It can be seen that with the increase of PeP voltage, the Sa value and Sz value at each concentration show an upward trend. However, compared with the unpolished sample, the Sa value and Sz value of the PeP polished sample are relatively low, showing a relatively higher surface smoothness. Under the same PeP voltage, with the increase of citric acid concentration, the Sa value and Sz value show a trend of first decreasing and then increasing, and when the citric acid concentration is 3wt%, the Sa value and Sz value are relatively low. It can be seen that when the citric acid concentration is 3wt%, the Sa value and Sz value reach the minimum value, so the citric acid concentration is preferably 2wt% to 4wt%, and more preferably 3wt%. The PeP voltage is preferably 240V to 250V, and more preferably 240V.
[0102] The average reflectivity and total reflection per unit area of the nano self-repairing aluminum alloy materials prepared under different citric acid concentrations and different PeP voltages are tested. The results are shown in Tables 5 and 6 and Figure 6 and Figure 7 .
[0103] Table 5 Average reflectivity (%) at different citric acid concentrations and different PeP voltages
[0104]
[0105] Table 6 Total reflection per unit area (lm / m 2 )
[0106]
[0107] As shown in Tables 5 and 6, Figure 6 and Figure 7 As shown in the figure, the average reflectivity shows a downward trend with the increase of PeP voltage, and shows a trend of first increasing and then decreasing with the increase of oxalic acid concentration. The average reflectivity is the highest when the voltage is 240V and the oxalic acid concentration is 3wt%, at which time the average reflectivity reaches 76.121% and the total reflection per unit area reaches 228.365lm / m 2 .
[0108] Example 8
[0109] A surface treatment method for an aluminum alloy material is basically the same as the method in Example 1, except that the PeP parameters are different, see Table 7.
[0110] Table 7 Comparison of reaction conditions with different PeP parameters
[0111]
[0112]
[0113] The surface roughness measurement results of nano self-repairing aluminum alloy materials prepared under different PeP parameters are shown in Tables 8 and 9 and Figure 8 and Fig. 9 .
[0114] Table 8 Sa values (μm) under different PeP parameters
[0115]
[0116] Table 9 Sz values under different PeP parameters (μm)
[0117]
[0118] Figure 8 and Fig. 9 The change trend of the arithmetic mean roughness of the surface of the aluminum alloy workpiece and the average height difference of the surface peaks and valleys with time under different PeP voltages is shown. Figure 8 and Fig. 9 It can be seen that with the increase of polishing time, the Sa and Sz values at each voltage show a trend of first decreasing and then stabilizing. And when the citric acid concentration is 3wt%, the Sa and Sz values are relatively low. It can be seen that when the polishing time is 5min, the Sa and Sz values reach the minimum value, so the citric acid concentration is preferably 4min to 6min, and more preferably 5min.
[0119] The average reflectivity and total reflection per unit area of the nano self-repairing aluminum alloy materials prepared under different PeP parameters are tested. The results are shown in Tables 10 and 11 and Fig.10 and Fig.11 .
[0120] Table 10 Average reflectivity under different PeP parameters (%)
[0121]
[0122] Table 11 Total reflection per unit area under different PeP parameters (lm / m 2 )
[0123]
[0124] As shown in Table 10 and Table 11 and Fig.10 and Fig.11As shown in the figure, the average reflectivity decreases with the increase of PeP voltage, and generally shows a trend of first increasing and then decreasing with the increase of polishing time. The average reflectivity is the highest when the voltage is 240V and the polishing time is 7min, at which time the average reflectivity reaches 76.045% and the total reflection per unit area reaches 228.135lm / m 2 .
[0125] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A surface treatment method for an aluminum alloy material, characterized in that: The following steps are involved: The aluminum alloy material to be polished is immersed in an electrolytic polishing liquid, and then the electrolyte plasma polishing is performed at 60 to 90° C. The voltage of the electrolyte plasma polishing is 240V to 320V to obtain a polished aluminum alloy material; The polyacrylic acid nano self-repairing material is coated on the surface of the polished aluminum alloy material, and the coating is cured to obtain the nano self-repairing aluminum alloy material; The mass percentage of polyacrylic acid in the polyacrylic acid nano self-repairing material is 10wt% to 50wt%.
2. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: The electrolytic polishing solution is obtained by dissolving an electrolyte in water; The electrolyte is obtained by mixing potassium chloride, ammonium chloride and organic acid; The concentration of potassium chloride in the electrolytic polishing solution is 10wt%; The concentration of ammonium chloride in the electrolytic polishing solution is 40wt%; The concentration of the organic acid in the electrolytic polishing solution is 1 to 5 wt %; The organic acid is citric acid or oxalic acid.
3. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: Polyacrylic acid nano self-healing material is obtained by mixing polyacrylic acid with water.
4. The surface treatment method of aluminum alloy material according to claim 3, characterized in that: The molecular weight of polyacrylic acid is 2000Da to 5000Da.
5. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: The temperature of electrolyte plasma polishing is 90℃±2℃.
6. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: The voltage of electrolyte plasma polishing is 240V~280V.
7. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: The time of electrolyte plasma polishing is 1min to 9min.
8. The surface treatment method of aluminum alloy material according to claim 1, characterized in that: The specific method of electrolyte plasma polishing is: The aluminum alloy material to be polished is connected to the anode of the power supply, and the conductive material is connected to the cathode of the power supply, and the aluminum alloy material to be polished and the conductive material are immersed in an electrolytic polishing liquid at 60 to 90° C., and then electrolyte plasma polishing is performed at a voltage of 200V to 400V to obtain a polished aluminum alloy material; The conductive material is titanium.
9. A nano self-repairing aluminum alloy material prepared by the surface treatment method according to any one of claims 1 to 8.
10. The nano self-repairing aluminum alloy material according to claim 9, characterized in that: The surface arithmetic mean roughness of the nano self-repairing aluminum alloy material is 0.1 to 0.2 μm; The average height difference between surface peaks and troughs is 2 to 4 μm.
